The Equity Myth: Racialization and Indigeneity at Canadian Universities - Henry, Frances; Kobayashi, Audrey Lynn; Smith, Malinda; Dua, Enakshi; James, Carl E.; Li, Peter; Ramos, Howard (UBC Press, 2017)
The university is often regarded as a bastion of liberal democracy where equity and diversity are vigorously promoted. In reality, the university still excludes many people and is a site of racialization that is subtle, complex, and sophisticated. This book, the first comprehensive, data-based study of racialized and Indigenous faculty members' experiences in Canadian universities, challenges the myth of equity in higher education. Drawing on a rich body of survey data, interviews, and analysis of universities' stated policies, leading scholars scrutinize what universities have done and question the effectiveness of their employment equity programs. They also make important recommendations as to how universities can address racialization and fulfill the promise of equity in the academy. --Publisher's description. Contents: Introduction : setting the context -- Representational analysis : comparing Canada, the United States, the United Kingdom, and Australia -- Differences in representation and employment income of racialized university professors in Canada -- Academic production, reward, and perceptions of racialized faculty members -- "Would never be hired these days" : the precarious work situation of racialized and indigenous faculty members -- The everyday world of racialized and indigenous faculty members in Canadian universities -- "You know why you were hired don't you?" Expectations and challenges in university appointments -- Shifting terrains : a picture of the institutionalization of equity in Canadian universities -- Mechanisms to address inequities in Canadian universities : the performativity of ineffectiveness -- Disciplinary silences : race, indigeneity, and gender in the social sciences -- A dirty dozen : unconscious race and gender biases in the academy -- Conclusion : challenging the myth. Includes bibliographical references (pages 328-355) and index.
Keywords: Canada Discrimination dans l'emploi; Canada Discrimination in employment. Discrimination in higher education. Equality. Indian college teachers. Race discrimination. Universities and colleges; Canada Discrimination raciale; Canada. Discrimination in employment; Canada. Discrimination in higher education; Canada. Equality; Canada. Race discrimination; Canada. Universities and colleges; Indian college teachers